Orange fluorescent glass material as well as preparation method and application thereof
By using an orange fluorescent glass material prepared with a sodium borosilicate glass matrix and a red nitride phosphor, the problems of high blue light overflow rate and difficult thermal management in LED automotive lighting systems are solved, and the effects of low blue light overflow rate, high light efficiency and good thermal conductivity are achieved.
Patent Information
- Application Number
- CN202510064763.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
In existing LED automotive lighting systems, the use of cold white light leads to a high blue light overflow rate, making it difficult to achieve suitable orange light effects, and the use of high-power LED devices increases thermal management challenges.
An orange fluorescent glass material consisting of a sodium borosilicate glass matrix and a nitride red phosphor is used. This material emits orange fluorescence under blue light excitation, with low blue light overflow rate, high light efficiency and good thermal conductivity.
The orange light effect with low blue light overflow rate and high light efficiency under blue light excitation is achieved, and the thermal management performance of high power LED lighting systems is improved through high thermal conductivity.
Smart Images

Figure CN119874182A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an orange fluorescent glass material and a preparation method and application thereof. Background Art
[0002] In the field of fourth-generation solid-state lighting, LED devices are widely used in indoor lighting, automotive lighting, display and other fields. Automotive lighting systems are also undergoing a transition from traditional bulbs to efficient and energy-saving LED technology. LED lighting sources usually emit cold white light (close to blue light), and the color temperature range of cold white light is usually between 5500 and 7500K. This is not applicable to car taillights and brake lights. The color temperature of automotive headlights is usually between 4300 and 6000K to ensure penetration and visual comfort, while the color temperature of car taillights is mainly red light, which requires a color temperature of 1500 to 2500K to ensure red at night and visual sensitivity. Not only the color temperature of the LED lighting fixtures formed should be considered, but also the blue light overflow rate, light efficiency, etc. In addition, long-distance lighting for automobiles requires the use of high-power LED devices.
[0003] As a new type of material, fluorescent glass has attracted wide attention in the application of LED automotive lighting systems. Fluorescent glass refers to a luminescent material prepared by doping fluorescent powder into a glass matrix. It has the optical properties of fluorescent powder and the heat resistance and transparency of glass. In LED applications, it can avoid the problems of aging and reduced efficiency caused by silicone encapsulation. The performance of the obtained fluorescent glass can be adjusted by adjusting the different types of doped fluorescent powders and the types of glass matrix.
[0004] CN114479859B discloses a germanate fluorescent glass ceramic and a preparation method thereof, which relates to the technical field of fluorescent material preparation for LED. 0.8 Ba 1.2 GeO4:Eu 2+ The orange fluorescent glass ceramic powder is mixed and hot-pressed to prepare a multi-color tunable germanate fluorescent glass ceramic containing white light, wherein: CaAl2O4:Eu 2+ The mass percentage of blue fluorescent microcrystals is: 0-20%; SrAl2O4:Eu 2+ The mass percentage of green fluorescent microcrystals is: 0-20%; CaAl 12 O 19 :Mn 4+ The mass percentage of red fluorescent microcrystals is: 0-20%; Sr 0.8 Ba 1.2 GeO4:Eu 2+ The mass percentage of the orange fluorescent glass ceramic is 40-100%. The obtained germanate fluorescent glass ceramic is an orange-red glass ceramic that can be excited by blue light or ultraviolet light.
[0005] CN110590158A discloses a borate fluorescent glass and its preparation method and application. The borate fluorescent glass is made of the following raw materials in percentage by mass: 10-30% rare earth oxide, 25-40% BaO and 40-60% B2O3; wherein the rare earth oxide is one or more of Eu2O3, Dy2O3, Tb4O7, Tm2O3 and Pr2O3. The preparation method comprises the following steps: ball milling, high temperature melting, pouring and annealing. The method can effectively solve the problem that fluorescent glass materials are difficult to achieve heavy doping with rare earth ions. The fluorescent glass prepared by the method can be effectively excited by near-ultraviolet and blue light. However, it does not involve orange fluorescent glass.
[0006] CN110698073A discloses a full-spectrum borosilicate fluorescent glass and a preparation method thereof, comprising a matrix glass and a full-spectrum fluorescent powder, wherein the matrix glass is prepared from raw materials of Na2O, ZnO, B2O3, SiO2 and CaO components; the mass molar fraction of each component of the matrix glass is: Na2O: 10-15%, ZnO: 20-35%, B2O3: 20-50%, SiO2: 0-20%, CaO: 0-20%; the full-spectrum fluorescent powder is composed of the following components: a cyan fluorescent powder having an emission peak of 480-500nm under blue light excitation, a green fluorescent powder having an emission peak of 520-540nm under blue light excitation, and a red fluorescent powder having an emission peak of 615-640nm under blue light excitation, and the molar percentage ratio of each component of the full-spectrum fluorescent powder is: cyan fluorescent powder: green fluorescent powder: red fluorescent powder = 1-1.5: 1.3-1.6: 0.3-0.7. Summary of the invention
[0007] An object of the present invention is to provide an orange fluorescent glass material, which can emit orange fluorescence under the excitation of blue light, has a low blue light overflow rate, high light efficiency, and good thermal conductivity.
[0008] Another object of the present invention is to provide a method for preparing the orange fluorescent glass material as described above.
[0009] Another object of the present invention is to provide a use of the orange fluorescent glass material as described above.
[0010] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0011] On the one hand, the present invention provides an orange fluorescent glass material, which is formed by a sodium borosilicate glass matrix and a nitride red fluorescent powder, wherein the mass ratio of the sodium borosilicate glass matrix to the nitride red fluorescent powder is 50-80:20-50;
[0012] The sodium borosilicate glass matrix has a chemical composition as shown in formula (1):
[0013] aB2O3·bSiO2·cNa2O·dCaO·eZnO(1),
[0014] Among them, a represents the molar coefficient of B2O3, 0.6≤a≤0.8; b represents the molar coefficient of SiO2, 0.1≤b≤0.2; c represents the molar coefficient of Na2O, 0.1≤c≤0.2; d represents the molar coefficient of CaO, 0.05≤d≤0.1; e represents the molar coefficient of ZnO, 0.05≤e≤0.1.
[0015] According to the orange fluorescent glass material of the present invention, preferably, the mass ratio of the sodium borosilicate glass matrix to the nitride red fluorescent powder is 65-75:25-35.
[0016] According to the orange fluorescent glass material of the present invention, preferably, 0.6≤a≤0.7, 0.1≤b≤0.15, 0.1≤c≤0.15, 0.05≤d≤0.08, and 0.07≤e≤0.09.
[0017] According to the orange fluorescent glass material of the present invention, preferably, the excitation wavelength of the orange fluorescent material is 350-500 nm, and the emission wavelength is 500-700 nm.
[0018] According to the orange fluorescent glass material of the present invention, preferably, the orange fluorescent material has a blue light overflow rate within a wavelength range of 380 to 460 nm of 5 to 17.5%.
[0019] On the other hand, the present invention also provides a method for preparing the orange fluorescent glass material as described above, comprising the following steps:
[0020] 1) According to the composition, a sodium borosilicate glass matrix and a nitride red phosphor are mixed to obtain a mixture;
[0021] 2) Sintering the mixture at 600-700° C. to obtain an orange fluorescent glass material.
[0022] According to the preparation method of the present invention, preferably, the sintering time is 10 to 40 minutes.
[0023] According to the preparation method of the present invention, preferably, it further comprises the steps of cutting and polishing the orange fluorescent glass material.
[0024] In another aspect, the present invention further provides a use of the above-mentioned orange fluorescent glass material in a vehicle LED lighting system.
[0025] In yet another aspect, the present invention further provides a vehicle LED lighting system, which comprises a blue light chip and a fluorescent layer, wherein the fluorescent layer comprises the orange fluorescent glass material as described above.
[0026] The orange fluorescent glass material of the present invention can emit orange fluorescence under the excitation of blue light, and the emission peak wavelength is 605nm. It can effectively convert the blue light part and reduce the overflow of high-energy harmful blue light; it has high light efficiency, good red ratio, and color temperature of 1750-1950K. In addition, it has high thermal conductivity and good thermal conductivity. It can be used for high-power automobile taillights and brake lights. The orange fluorescent glass material of the present invention has a low sintering temperature of 600-700°C when it is prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The emission spectra of the orange fluorescent glass materials obtained in Comparative Examples 1 to 4 and Examples 1 to 4 are shown.
[0028] Figure 2 The excitation spectra of the orange fluorescent glass materials obtained in Comparative Examples 1 to 4 and Examples 1 to 4 are shown.
[0029] Figure 3 The UV-visible light transmittance test curves of the orange fluorescent glass materials obtained in Comparative Examples 1 to 4 and Examples 1 to 4 are shown.
[0030] Figure 1 , Figure 2 , Figure 3 2%, 5%, 10%, 15%, 20%, 30%, 40% and 50% refer to Comparative Examples 1 to 4 and Examples 1 to 4, respectively. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0032] <Orange fluorescent glass material>
[0033] The orange fluorescent glass material provided by the present invention is formed by a sodium borosilicate glass matrix and a nitride red fluorescent powder, wherein the mass ratio of the sodium borosilicate glass matrix to the nitride red fluorescent powder is 50-80:20-50;
[0034] The sodium borosilicate glass matrix has a chemical composition as shown in formula (1):
[0035] aB2O3·bSiO2·cNa2O·dCaO·eZnO(1),
[0036] Wherein, a represents the molar coefficient of B2O3, 0.6≤a≤0.8; b represents the molar coefficient of SiO2, 0.1≤b≤0.2; c represents the molar coefficient of Na2O, 0.1≤c≤0.2; d represents the molar coefficient of CaO, 0.05≤d≤0.1; e represents the molar coefficient of ZnO, 0.05≤e≤0.1. Such orange fluorescent glass material can emit orange fluorescence under the excitation of blue light, with low blue light overflow rate and high light efficiency. It can be used in the taillights and brake lights of automobile lighting systems, and packaged with blue light chips to achieve high-power and efficient lighting of about 3W.
[0037] The orange fluorescent glass material of the present invention consists only of the above components and inevitable impurities.
[0038] In the sodium borosilicate glass matrix, a represents the molar coefficient of B2O3, 0.6≤a≤0.8, preferably, 0.6≤a≤0.7, more preferably, 0.6≤a≤0.65; B2O3 is boron trioxide. b represents the molar coefficient of SiO2, 0.1≤b≤0.2, preferably, 0.1≤b≤0.18, more preferably, 0.1≤b≤0.15, more preferably, 0.12≤b≤0.15; SiO2 is silicon dioxide. c represents the molar coefficient of Na2O, 0.1≤c≤0.2, preferably, 0.1≤c≤0.18, more preferably, 0.1≤c≤0.15; Na2O is sodium oxide. d represents the molar coefficient of CaO, 0.05≤d≤0.1, preferably, 0.05≤d≤0.08, more preferably, 0.05≤d≤0.06; CaO is calcium oxide. e represents the molar coefficient of ZnO, 0.05≤e≤0.1, preferably, 0.06≤e≤0.1, more preferably, 0.07≤e≤0.09. ZnO is zinc oxide. Such a sodium borosilicate glass matrix is more conducive to improving the luminescent properties of the obtained orange fluorescent glass, and can reduce the sintering temperature during manufacturing, thereby achieving matching between the nitride phosphor / glass matrix and the sintering temperature.
[0039] According to a specific embodiment of the present invention, the orange fluorescent glass material has the following chemical composition: 0.6B2O3·0.12SiO2·0.15Na2O·0.05CaO·0.08ZnO.
[0040] In the present invention, the nitride red phosphor can be any common one, including but not limited to M2Si5N8:Eu 2+ (M=Ca, Sr, Ba). It can be purchased commercially. According to a specific embodiment of the present invention, the nitride red phosphor is purchased from Xi'an Hongyu Optoelectronics Technology Co., Ltd.
[0041] In the present invention, the mass ratio of the sodium borosilicate glass matrix and the nitride red phosphor is 50-80:20-50, preferably 55-75:25-45, more preferably 60-75:25-40, and even more preferably 65-75:25-35. For example, it can be 70:30. If the mass ratio of the two is not within the scope of the present invention, the harmful blue light overflow rate will increase, the light efficiency will be reduced, and the red ratio is not within the scope of the present invention.
[0042] The absorption band of the orange fluorescent glass of the present invention in the range of ultraviolet-visible light of 250 to 1000 nm is 380 to 460 nm.
[0043] The excitation wavelength of the orange fluorescent glass material of the present invention is 350-500 nm, preferably, the excitation wavelength is at 450 nm. The emission wavelength is 500-700 nm, preferably, the strongest peak appears at 605 nm.
[0044] The orange fluorescent glass material of the present invention has a blue light overflow rate of 5 to 17.5% within the wavelength range of 380 to 460 nm. Preferably, the blue light overflow rate (ie, blue light overflow rate) can be as low as below 15.5%.
[0045] The thermal conductivity of the orange fluorescent glass material of the present invention is 0.3 W·m -1 ·K -1 above.
[0046] The orange fluorescent glass material of the present invention has a blue light overflow rate lower than 17.5%, a light efficiency greater than 61.0 lm / W, and a red ratio greater than 34.5%.
[0047] <Preparation method>
[0048] The present invention also provides a method for preparing the orange fluorescent glass material as described above, comprising the following steps: 1) a mixing step; 2) a sintering step. Optionally, it also includes cutting and polishing steps. The following is a detailed description.
[0049] Mixing Steps
[0050] According to the above composition, the sodium borosilicate glass matrix and the nitride red phosphor are mixed to obtain a mixture. During the mixing, the mixture can be ground in an agate mortar for 10 to 60 minutes, preferably 15 to 50 minutes, and more preferably 30 to 40 minutes.
[0051] The sodium borosilicate glass matrix is obtained by mixing the components B2O3, SiO2, Na2O, CaO and ZnO. The sodium borosilicate glass matrix is powder.
[0052] Sintering steps
[0053] The mixture is sintered at 600-700° C. to obtain an orange fluorescent glass material. Compared with the prior art, the present invention can control a lower sintering temperature.
[0054] In the present invention, the sintering temperature may be 600 to 700° C., preferably 600 to 680° C., more preferably 600 to 650° C. The sintering time may be 10 to 40 min, preferably 15 to 40 min, more preferably 25 to 35 min.
[0055] In the present invention, the heating rate when the mixture is sintered may be 3 to 15° C. / min, preferably 5 to 12° C. / min, and more preferably 7 to 10° C. / min.
[0056] In the present invention, the sintering may be followed by cooling to room temperature.
[0057] Cutting and polishing steps
[0058] The obtained orange fluorescent glass material is cut and polished to obtain a fluorescent glass material that can be packaged in an LED lamp and plays a light conversion role.
[0059] The cutting thickness may be 0.2 to 1.0 mm, preferably 0.3 to 0.7 mm, and more preferably 0.3 to 0.5 mm. The cutting may be performed in a single-wire saw, and the polishing may be performed in a polishing machine.
[0060] <Purpose>
[0061] The present invention also provides a use of the orange fluorescent glass material, specifically a use in a vehicle LED lighting system, especially a use in a vehicle taillight and a brake light.
[0062] <Automotive LED Lighting System>
[0063] The present invention also provides a vehicle LED lighting system, which includes a blue light chip and a fluorescent layer, wherein the fluorescent layer includes the orange fluorescent glass material as described above. First, the above orange fluorescent glass material is cut, ground and polished. Then, the orange fluorescent glass material is fixed on a special bracket, and is glued and sealed with the blue light LED chip by thermal conductive silicone grease to ensure waterproof, dustproof and high temperature resistance. Subsequently, heat treatment is performed to enhance the firmness of the package to ensure that the orange fluorescent glass material is stable under high temperature and vibration conditions. Finally, the light source and the circuit are connected, and the final assembly and functional testing are performed to ensure the optical performance and reliability of the LED lamp.
[0064] Test method:
[0065] The transmittance is measured by a UH4150 UV-Vis spectrophotometer with a scanning range of 250 to 800 nm. The blue light overflow rate is the light transmittance within the range of 380 to 460 nm. The smaller the blue light overflow rate, the more harmful blue light is converted into orange light by the fluorescent glass, and the higher the light conversion efficiency.
[0066] Fluorescence spectroscopy was performed using an Edinburgh FLS1000 fluorescence spectrometer, with a xenon lamp as the excitation light source and a scanning range of 480 to 800 nm.
[0067] The photoelectric color performance (luminous efficiency, color temperature, red ratio) of LED lighting fixtures for car lights adopts HASS2000 with a scanning range of 350 to 1000nm.
[0068] Thermal conductivity is tested using a TC3200 thermal conductivity meter. Preheat the system first, then clamp the sensor with two samples of the same specifications and fix them with weights. Set the test interval to 3 minutes and the acquisition time to 5 seconds in the software, perform "thermal conductivity measurement", repeat 3 times, take the average value, and get the thermal conductivity value of the fluorescent glass.
[0069] In the following examples, the nitride red phosphor is M2Si5N8:Eu 2+ (M=Ca, Sr, Ba) system, purchased from Xi'an Hongyu Optoelectronics Technology Co., Ltd.
[0070] Comparative Example 1
[0071] A sodium borosilicate glass matrix and a nitride red phosphor with a chemical composition of 0.6B2O3·0.12SiO2·0.15Na2O·0.05CaO·0.08ZnO (i.e., a=0.6, b=0.12, c=0.15, d=0.05, e=0.08, a, b, c, d, e are corresponding molar coefficients) are provided. The sodium borosilicate glass matrix and the nitride red phosphor are mixed at a mass ratio of 98:2, and the mixture is fully ground in an agate mortar for 30 minutes to obtain a mixture.
[0072] The mixture was put into a crucible, and then the crucible was placed in a muffle furnace, heated to 610°C at a heating rate of 10°C / min, sintered at 610°C for 30 minutes, and naturally cooled to room temperature in the furnace to obtain an orange fluorescent glass material.
[0073] The obtained orange fluorescent glass material can be cut and polished to obtain an orange fluorescent glass material that can be packaged in an automotive LED lamp and used as a light conversion fluorescent glass material. The thickness after polishing is 0.3 mm.
[0074] The performance test of orange fluorescent glass material is shown in Table 1.
[0075] Comparative Example 2
[0076] In this comparative example, the mass ratio of the sodium borosilicate glass matrix to the nitride red phosphor is 95:5. The remaining operation steps and process parameters are the same as those of comparative example 1.
[0077] Comparative Example 3
[0078] In this comparative example, the mass ratio of the sodium borosilicate glass matrix to the nitride red phosphor is 90:10. The remaining operation steps and process parameters are the same as those of comparative example 1.
[0079] Comparative Example 4
[0080] In this comparative example, the mass ratio of the sodium borosilicate glass matrix to the nitride red phosphor is 85:15. The remaining operation steps and process parameters are the same as those of comparative example 1.
[0081] Example 1
[0082] In this embodiment, the mass ratio of the sodium borosilicate glass matrix to the nitride red phosphor is 80:20. The remaining operation steps and process parameters are the same as those of Comparative Example 1. The specific steps are as follows:
[0083] A sodium borosilicate glass matrix and a nitride red phosphor with a chemical composition of 0.6B2O3·0.12SiO2·0.15Na2O·0.05CaO·0.08ZnO (i.e., a=0.6, b=0.12, c=0.15, d=0.05, e=0.08, a, b, c, d, e are corresponding molar coefficients) are provided. The sodium borosilicate glass matrix and the nitride red phosphor are mixed at a mass ratio of 80:20, and the mixture is fully ground in an agate mortar for 30 minutes to obtain a mixture.
[0084] The mixture was put into a crucible, and then the crucible was placed in a muffle furnace, heated to 610°C at a heating rate of 10°C / min, sintered at 610°C for 30 minutes, and naturally cooled to room temperature in the furnace to obtain an orange fluorescent glass material.
[0085] The obtained orange fluorescent glass material can be cut and polished to obtain an orange fluorescent glass material that can be packaged in an automotive LED lamp and used as a light conversion fluorescent glass material. The thickness after polishing is 0.3 mm.
[0086] The performance test of orange fluorescent glass material is shown in Table 1.
[0087] Example 2
[0088] In this embodiment, the mass ratio of the sodium borosilicate glass matrix to the nitride red phosphor is 70:30. The remaining operation steps and process parameters are the same as those of Comparative Example 1.
[0089] Example 3
[0090] In this embodiment, the mass ratio of the sodium borosilicate glass matrix to the nitride red phosphor is 60:40. The remaining operation steps and process parameters are the same as those of Comparative Example 1.
[0091] Example 4
[0092] In this embodiment, the mass ratio of the sodium borosilicate glass matrix to the nitride red phosphor is 50:50. The remaining operation steps and process parameters are the same as those of Comparative Example 1.
[0093] Table 1
[0094]
[0095] Note: In Table 1, the mass ratio refers to the mass ratio of sodium borosilicate glass matrix to nitride red phosphor.
[0096] The excitation spectra of the orange fluorescent glass materials obtained in Comparative Examples 1 to 4 and Examples 1 to 4 are shown in FIG. Figure 1 , emission spectrum see Figure 2 , UV-visible light transmittance results are shown in Figure 3 . Figure 1 , Figure 2 , Figure 3 2%, 5%, 10%, 15%, 20%, 30%, 40%, 50% refer to Comparative Examples 1 to Comparative Examples 4 and Examples 1 to Examples 4, respectively. As can be seen from the figure, the wavelength range of the excitation spectrum is 380-460nm, and the peak of the emission spectrum is 605nm. By changing the mass ratio of the nitride red phosphor to the sodium borosilicate glass matrix, the luminous intensity of the resulting orange fluorescent glass material changes, and at the same time affects the blue light overflow rate in the range of 380-460nm, thereby affecting the photoelectric color performance of the LED lamp. With the increase of the mass concentration of the nitride red phosphor, the blue light overflow rate of the resulting orange fluorescent glass in the range of 380-460nm gradually decreases, producing orange light with a peak value of 605nm, effectively achieving the purpose of light conversion.
[0097] At the same time, we measured the thermal conductivity of the orange fluorescent glass of Example 2 to be 0.33 W·m -1 ·K -1 Much higher than the thermal conductivity of nitride red phosphors 0.14W·m -1 ·K -1Specifically, materials with high thermal conductivity can transfer heat from high-temperature areas to low-temperature areas more quickly during the heat transfer process, thus preventing the workpiece from being overheated and melted and damaged.
[0098] The orange fluorescent glass materials obtained in Comparative Examples 1 to Comparative Examples 4 and Examples 1 to 4 were packaged according to the above steps to form LED lighting fixtures, and the relevant performance (including luminous efficiency, color temperature, and red ratio) under about 3W high-power operation was characterized, and the results are shown in Table 1. As can be seen from Table 1, with the increase of the doping concentration of the nitride red phosphor, the luminous efficiency gradually increases, the red ratio increases, and the color rendering properties of high-efficiency orange fluorescence can be achieved.
[0099] In Examples 1 to 4, the blue light overflow rate is lower than 17.5%, the luminous efficiency is greater than 61.0 lm / W, and the red ratio is greater than 34.5%.
[0100] Comprehensively evaluating the orange fluorescent glass materials obtained from Comparative Examples 1 to 4 and Examples 1 to 4, considering the fluorescence intensity, luminous efficiency, color rendering and cost, the orange fluorescent glass material of Example 2 is the best and more suitable for use in high-power and high-color rendering automobile taillight lighting systems.
[0101] Embodiments 5 to 8
[0102] The orange fluorescent glass material samples obtained in Example 2 were cut, polished and ground to different thicknesses, namely 0.1 mm (Example 5), 0.5 mm (Example 6), 0.7 mm (Example 7), and 0.9 mm (Example 8). A blue LED chip was used as a light source, and the fluorescent glass material was packaged to form an LED lighting fixture, and the performance was tested. Among them, the thickness in Example 2 was 0.3 mm.
[0103] The results are shown in Table 2.
[0104] Table 2
[0105]
[0106] It can be seen from Table 2 that by adjusting the thickness of the obtained orange fluorescent glass, different light effects and color temperatures can be effectively controlled, the colors of car taillights and brake lights can be better restored, and the recognition can be improved, which is beneficial to effectively improve traffic safety in different scenarios.
[0107] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. An orange fluorescent glass material, characterized in that: It is formed by a sodium borosilicate glass matrix and a nitride red phosphor, and the mass ratio of the sodium borosilicate glass matrix to the nitride red phosphor is 50-80:20-50; The sodium borosilicate glass matrix has a chemical composition as shown in formula (1): aB2O3·bSiO2·cNa2O·dCaO·eZnO(1), Among them, a represents the molar coefficient of B2O3, 0.6≤a≤0.8; b represents the molar coefficient of SiO2, 0.1≤b≤0.2; c represents the molar coefficient of Na2O, 0.1≤c≤0.2; d represents the molar coefficient of CaO, 0.05≤d≤0.1; e represents the molar coefficient of ZnO, 0.05≤e≤0.
1.
2. The orange fluorescent glass material according to claim 1, characterized in that: The mass ratio of the sodium borosilicate glass matrix to the nitride red phosphor is 65-75:25-35.
3. The orange fluorescent glass material according to claim 1, characterized in that: 0.6≤a≤0.7, 0.1≤b≤0.15, 0.1≤c≤0.15, 0.05≤d≤0.08, 0.07≤e≤0.
09.
4. The orange fluorescent glass material according to claim 1, characterized in that: The excitation wavelength of the orange fluorescent material is 350-500nm, and the emission wavelength is 500-700nm.
5. The orange fluorescent glass material according to claim 1, characterized in that: The orange fluorescent material has an overflow rate of 5 to 17.5% for blue light within a wavelength range of 380 to 460 nm.
6. A method for preparing the orange fluorescent glass material according to any one of claims 1 to 5, characterized in that: The steps include: 1) According to the composition, a sodium borosilicate glass matrix and a nitride red phosphor are mixed to obtain a mixture; 2) Sintering the mixture at 600-700° C. to obtain an orange fluorescent glass material.
7. The preparation method according to claim 6, characterized in that: The sintering time is 10 to 40 minutes.
8. The preparation method according to claim 7, characterized in that: The method also includes the steps of cutting and polishing the orange fluorescent glass material.
9. Use of the orange fluorescent glass material according to any one of claims 1 to 6 in a vehicle LED lighting system.
10. A vehicle LED lighting system, characterized in that: It comprises a blue light chip and a fluorescent layer, wherein the fluorescent layer comprises the orange fluorescent glass material as claimed in any one of claims 1 to 6.
Citation Information
Patent Citations
Oxynitrides luminescent material and illuminating or exhibiting light source produced thereby
CN101117576A
Preparation method for nitride phosphor / glass composite luminescent sheet layer
CN103819091A
Full-spectrum borosilicate fluorescent glass and preparation method thereof
CN110698073A
LED light source capable of weakening blue light harm and manufacturing method thereof
CN111326643A
Pigment with day-light fluorescence
CN1337988A